PERSPECTIVES OF HAJJ AND UMRAH ORGANIZERS DURING A PANDEMIC ON GOVERNANCE, FACILITIES, STRATEGIES AND COMPETITIVE ADVANTAGE - Selfiani (Universitas Mathla’ul Anwar Banten, 2022)
The research aims to analyze and examine the effect of governance on competitive advantage, to analyze and examine the effect of facilities on competitive advantage, to analyze and examine the effect of strategy moderating the relationship between governance and competitive advantage. .to analyze and examine the effect of strategy on competitive advantage. The sample in this study were employees of the Hajj and Umrah organizers at the Jakarta Regional Office. The research used is a questionnaire (questionnaire), with a Likert scale using validation and reliability tests. The results of this study indicate that governance has a positive effect on competitive advantage, facilities have a positive effect on competitive advantage, and strategies for moderating the relationship between governance and competitive advantage. strategy moderates the relationship between facilities and competitive advantage. strategy has a positive effect on competitive advantage. The limitation of the study is that the sample used has not been able to conclude the results of the study as a whole due to incomplete sampling in the population area because it is limited to one area. The implications of the research are contributing to the concept of developing the factors that affect business continuity, improving business strategies, and increasing revenue for hajj and umrah travel service bureaus